2020
DOI: 10.1098/rsos.200485
|View full text |Cite
|
Sign up to set email alerts
|

Moisture alone is sufficient to impart strength but not weathering resistance to termite mound soil

Abstract: Soil is used for the construction of structures by many animals, at times admixed with endogenous secretions. These additives, along with soil components, are suggested to have a role in biocementation. However, the relative contribution of endogenous and exogenous materials to soil strength has not been adequately established. Termite mounds are earthen structures with exceptional strength and durability including weathering resistance to wind and rain. With in situ and laboratory-base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 41 publications
0
12
0
Order By: Relevance
“…electronic supplementary material, figure S5. It consists of inorganic and organic materials admixed with endogenous secretions made of lignin and cellulose, originally from the plant cell walls [1,10,13,20,22] and which show up at wavelengths of paraffins-distinctly related to terpenes and resins (cf. figure 2b).…”
Section: Different Densitiesmentioning
confidence: 99%
See 4 more Smart Citations
“…electronic supplementary material, figure S5. It consists of inorganic and organic materials admixed with endogenous secretions made of lignin and cellulose, originally from the plant cell walls [1,10,13,20,22] and which show up at wavelengths of paraffins-distinctly related to terpenes and resins (cf. figure 2b).…”
Section: Different Densitiesmentioning
confidence: 99%
“…For comparison, the global compressive strength of load supporting walls at foraging sites of Coptotermes acinaciformis were estimated to be 0.22 MPa, much lower than concrete, indicating that there might be a difference between the nest where highest safety is required and the foraging site where the termites invest just as much energy as necessary [10,20]. However, the strength of soil depends on mineral composition, grain size distribution and the ratio of clay/silt and other particles/materials, degree of saturation (water in interparticle junctions and related water surface tension), stress history [21,22]. Zachariah et al [23] showed for O. obesus that construction particle choice being close to its liquid limit attained high compressive strength similar to that of mounds found in the field when dry, by forming a monolithic, densely packed structure.…”
Section: Fine Grain Termite Bricksmentioning
confidence: 99%
See 3 more Smart Citations